2008
DOI: 10.1002/elan.200704134
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Properties of Contactless Conductivity and Diode‐Array Photometric Detectors in Analyses of Low‐Molecular, Biologically Active Substances by Capillary Electrophoresis in Acetic Acid Solutions

Abstract: The performance of the contactless conductivity (C 4 D) and diode array photometric (DAD) detectors has been compared for CE separations of creatinine, arginine and 3-methylhistidine in acetic acid background electrolytes. The contactless conductivity detector response has also been modeled. It has been found that the two detectors provide similar responses and can readily be used for dual CE detection. Changes in the acetic acid concentration affect the C 4 D noise less than the DAD noise, but their effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Also, the response of CCD is strongly dependent on parameters such as effective mobility of BGE constituents and its conductivity. Opekar et al studied the effect of capillary diameter on CCD performance and they found that 75 μm id provides the best response regarding detection limits . For such reasons the same capillary diameter was employed in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the response of CCD is strongly dependent on parameters such as effective mobility of BGE constituents and its conductivity. Opekar et al studied the effect of capillary diameter on CCD performance and they found that 75 μm id provides the best response regarding detection limits . For such reasons the same capillary diameter was employed in this work.…”
Section: Resultsmentioning
confidence: 99%
“…5 in [15]). This is parasitic signal transfer between the electrodes and it can be seen in Figure 2 that the experimental dependences confirm the modeling results, the crosstalk capacitance is not affected by the capillary wall thickness.…”
Section: A Comparison Of the Calibration Dependences For The Thick-anmentioning
confidence: 94%
“…It follows from these dependences that the response first rapidly increases with increasing MES/His concentration, attains a maximum and then slowly decreases. This course is characteristic of C 4 D, whose conductivity response is a complex function of both the BGE conductivity and the permittivity (for details see [15]). The decrease in the sensitivity at higher BGE concentrations also follows from the detection cell calibration (see Fig.…”
Section: Ce Separation Of a Kmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, a combination of two independent detection techniques is tested, namely, the universal C 4 D and selective UV photometry. The C 4 D/UV combination has already been used several times in CE, for determination of model samples of cyclodextrins and their derivatives [29], for analyses of mixtures of creatinine (Crea), 3-methylhistidine and arginine [30], for quantitation of mixed peaks of amino acids in a vitamin complement hydrolyzate [31], for determination of inorganic cations and organic acids in a multivitamin complement [32], and for determination of inorganic and organic anions in white wine [33]. To our knowledge, the C 4 D/UV combination has not yet been applied to analyses of OA profiles in complex clinical samples.…”
Section: Introductionmentioning
confidence: 99%